FRI0465 PREDICTION OF INCIDENT FRAGILITY FRACTURES THROUGH RADIOFREQUENCY ECHOGRAPHIC MULTI SPECTROMETRY(REMS). (June 2019) - Adami, Giovanni; Arioli, Giovanni; Bianchi, Gerolamo; Brandi, Maria Luisa; Caffarelli, Carla; Casciaro, Sergio; Cavalli, Loredana; Cianferotti, Luisella; Conversano, Francesco; Giusti, Andrea; Gonnelli, Stefano; Grimaldi, Antonella; et al.
Abstract : Background: Radiofrequency Echographic Multi Spectrometry (REMS) is an innovative non-ionizing technique used for diagnosing osteoporosis at lumbar spine and femoral neck sites. In accordance with the results of a multicentre clinical study, REMS T-score values were highly correlated with Dual-energy X-ray absorptiometry (DXA) T-scores [1]. Objectives: To determine the predictive value in term of fragility fracture risk reduction of the REMS T-score compared to DXA T-score in a representative female population. Methods: We enrolled 1370 women (30-90 y, BMI ≤ 35 kg/m 2 ) from 2013 to 2017. We performed in all patients both DXA and REMS lumbar scans. All analyses were performed under the strictest adherence to the corresponding guidelines. All patients underwent a follow-up lasting up to 5 years to assess the incidence of fragility fractures. Patients were stratified in two groups: patients who suffered a fragility fracture during the follow-up period (Group X) and those who did not (Group Y). Through an iterative process, the two groups were then age-matched with an enrolment proportion of 1:2. The finally obtained groups were identified as Group A (with incident fractures) and Group B (without incident fractures). The performance of REMS T-score in discriminating between Group A and Group B was quantitatively assessed and compared with DXA. Results: Fragility fractures incidence was 14.0% (192 out of 1370 patients, mean follow-up 3.6 ± 0.8 years). Group A included 180 patients (mean age 67.2 ± 7.2 years) and Group B included 360 patients (mean age 67.3 ± 3.5 y). Group A and Group B did not show significant differences with respect to height (p=0.41), weight (p=0.68) and BMI (p=0.32). As expected we found significant differences in REMS T-score (-2.68 ± 1.28 in Group A vs -2.03 ± 1.23 in Group B, p<0.001) and DXA T-score (-2.52 ± 1.20 in Group A vs -2.08 ± 1.17 in Group B, p<0.001). REMS T-score ≤ -2.5 identified Group A patients with sensitivity = 65% and specificity = 58% (OR=2.6). DXA T-score identified Group A patients with sensitivity = 57% and specificity = 57% (OR=1.7). Conclusion: REMS T-score resulted an effective predictor for the risk of incident fragility fractures in a representative population-based sample of female subjects. Reported OR values showed also that REMS had a better performance than DXA in the considered population, showing higher values for both sensitivity and specificity in the identification of fragile patients. References: [1] Di Paola M, Gatti D, Viapiana O, et al. Radiofrequency echographic multispectrometry compared with dual X-ray absorptiometry for osteoporosis diagnosis on lumbar spine and femoral neck. Osteoporos IntPublished Online First: 4 September 2018. Doi:10.1007/s00198-018-4686-3 Disclosure of Interests: Giovanni Adami: None declared, Giovanni Arioli: None declared, Gerolamo Bianchi: None declared, Maria Luisa Brandi: None declared, Carla Caffarelli: None declared, Sergio Casciaro Shareholder of: Sergio Casciaro owns stocks of Echolight Spa., Loredana Cavalli: None declared, Luisella Cianferotti Speakers bureau: Abiogen Pharma, Bruno Farmaceutici, Shire, Francesco Conversano Shareholder of: Francesco Conversano own stocks of Echolight Spa, Andrea Giusti: None declared, Stefano Gonnelli: None declared, Antonella Grimaldi: None declared, Maurizio Muratore: None declared, Daniele Perrone: None declared, Paola Pisani: None declared, Eugenio Quarta: None declared, Davide Gatti Speakers bureau: Abiogen, Amgen, Janssen-Cilag, Mundipharma, Pfeizer